2020
DOI: 10.1590/1414-431x20198969
|View full text |Cite
|
Sign up to set email alerts
|

Repercussions of adjuvant-induced arthritis on body composition, soleus muscle, and heart muscle of rats

Abstract: This study investigated the repercussions of adjuvant-induced arthritis (AIA) on body composition and the structural organization of the soleus and cardiac muscles, including their vascularization, at different times of disease manifestation. Male rats were submitted to AIA induction by intradermal administration of 100 mL of Mycobacterium tuberculosis (50 mg/mL), in the right hind paw. Animals submitted to AIA were studied 4 (AIA4), 15 (AIA15), and 40 (AIA40) days after AIA induction as well as a control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The paws sections of rats administered with high dose (300 mg/Kg RBW) of acetogeninrich extract of avocado pulp (Figure3 J, K & L) showed normal thin epidermis (arrow) and skin appendages (*) (Fig.3 J), normal skin layers with absence of subepidermal inflammatory reaction (*) (Fig.3 K), marked reduction in the inflammatory cells infiltration, preserved articular cartilage (C), regular bone marrow (Bm), and reduced synovial hyperplasia (Fig.3 L). The present results are in accordance with the results of many previous studies[49,[58][59][60].…”
supporting
confidence: 94%
“…The paws sections of rats administered with high dose (300 mg/Kg RBW) of acetogeninrich extract of avocado pulp (Figure3 J, K & L) showed normal thin epidermis (arrow) and skin appendages (*) (Fig.3 J), normal skin layers with absence of subepidermal inflammatory reaction (*) (Fig.3 K), marked reduction in the inflammatory cells infiltration, preserved articular cartilage (C), regular bone marrow (Bm), and reduced synovial hyperplasia (Fig.3 L). The present results are in accordance with the results of many previous studies[49,[58][59][60].…”
supporting
confidence: 94%
“…The AIA-induced reduction in body weight, observed in animals submitted or not to ORX, indicates sarcopenia, a condition commonly described in this arthritis model. Moreover, a previous study revealed that sarcopenia is more severe at the moment when the animals of the present study were assessed ( 20 ).…”
Section: Discussionmentioning
confidence: 57%
“…Like in the present study, those authors harvest aortas on the 21st day after the onset of AIA in the paw contralateral to the induction. We chose to harvest the aortas at this time, as we had already observed that AIA-related joint volume increment is higher at this moment ( 20 ). It is noteworthy, however, that AIA is a reversible model of arthritis, in which the apex of increased joint volume is not necessarily reached at the moment when inflammatory activity is at its highest.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is used to monitor the effectiveness of the treatment. For example, Pita et al (2020) reported a significant increase in paw swelling on the 4th and 15th days after FCA induction, which persisted during the entire duration of the study (41 days) in the positive control group. The same trend is observed in the present research, the positive control group possesses higher paw swelling throughout the entire study trial.…”
Section: Discussionmentioning
confidence: 95%